Quality of life of elderly people living in a retirement home - Čanković, Sonja; Ač Nikolić, Eržebet; Mijatović Jovanović, Vesna; Kvrgić, Svetlana; Harhaji, Sanja; Radić, Ivana (Vojnosanitetski pregled, 2017)
Background/Aim. The World Health Organization (WHO) identified four broad domains as being universally relevant to the quality of life, namely physical, and psychological health, social relationships, and environment. The aim of this study was to assess the relationship between sociodemographic characteristics and quality of life of old people. Methods. The World Health Organization Quality of Life BREF questionnaire (WHOQOL-BREF) was used to assess quality of life on a random sample of 200 people aged 60 years and over who lived in the Retirement Home in Novi Sad. Items within the questionnaire were organized into four domains: physical, psychological, social relationships and environment. Results. The majority of the participants were women (69.8%). The mean age was 79.2 years (SD = 6.6 years).  Most of them were widowed (73.4%). More than two thirds of participants (68.8%) reported that they were ill at that moment and almost half of them (48.8%) had cardiovascular, 18.5% musculoskeletal, 9.6% endocrine and 5.9% neurological disease. In the social relations domain scores were lower in males (t = 2.4; p = 0.017). Scores of other domains did not differ significantly with regard to the age, educational level and the marital status of the participants. Participants who reported the presence of a disease had significantly lower mean scores of physical, psychological and environment domain. Conclusion. The presence of disease is a relevant factor for quality of life, whereas age, education and marital status do not reflect on physical health, psychological and environmental domain of quality of life.
Keywords: aged; homes for the aged; quality of life; questionnaires; serbia